Association between violence, stress and academy performance in 1º and 6º year of medical students of a public university, 2017 - Barahona-Meza, Lorenzo (2018)
Introduction. There are national and international reports of the presence of stress in medical students, higher than in other professional careers; likewise, the presence of stress is related to low academic performance. Objective. To determine if there is an association between violence, stress and the academic performance of the first and sixth year medical students of the National University of San Marcos. Methods. It was surveyed 109 (47%) students of the 6th year, and 122 (53%) students of the 1st year. The perception of violence and stress were determined with validated instruments; academic performance was determined by the annual weighted average. The Mann Whitney U test was used to establish differences between the means of the quantitative variables. To establish the correlation between the study variables, the Spearman correlation coefficient was used. Values p <0,05 were considered significant. Results. The perception of violence was higher in 6th grade students. Positive correlation was established between stress and violence in 6th grade students. Conclusion. In both groups studied, perception of violence was determined, higher in 6th grade students. The correlation between violence and stress was significant only in 6th grade students. There was no significantassociation of stress and violence with academic performance.